The Effectiveness of Implementing the Cooperatif Learning Model Type Think Pair Share (TPS) in Mathematics Learning - Aliyah Khairunnisa; Muhammad Darwis; Syahrullah Asyari (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2026)
This study aimed to evaluate the effectiveness of the Think Pair Share (TPS) cooperative learning model in improving seventh-grade students’ mathematics achievement at SMPIT Ar-Rahmah Makassar. The urgency of this study stems from the persistently low mathematics learning outcomes, particularly in the topic of linear equations in one variable (PLSV), and the dominance of lecture-based methods that fail to actively engage students. This pre-experimental study involved 51 students from two classes (Al-Kindi Putra and Ibnu Thufail Putri) and tested TPS within the school’s unique leadership-based curriculum. Data were collected through observation, pretest-posttest, and student response questionnaires, and analyzed descriptively and inferentially using a One Sample T-Test. The findings revealed that the average posttest scores exceeded the minimum mastery criteria (72), N-Gain scores were in the medium category (0.30 ≤ g < 0.70), student activity was categorized as active (score > 2.5), and student responses were positive (score > 60). These results demonstrate that TPS facilitates active and collaborative learning that significantly improves mathematics understanding, and it is therefore recommended for integration into other subjects with appropriate teacher training support.